Feasibility Test of “Auxora” Ready-To-Wear Clothing with Weaving Techniques - Aqilah Putri Hardianti; Irmayanti Irmayanti (Jurnal Penelitian Pendidikan, 2026)
The rapid development of the fashion industry encourages various design innovations in ready-to-wear products. One innovation that can be applied is the use of weaving techniques as an aesthetic element that enhances visual value while incorporating cultural identity into fashion products. This study aimed to develop and determine the feasibility of the "Auxora" ready-to-wear garment using weaving techniques inspired by the woven bamboo walls of traditional Sundanese houses. The research employed a development method using the PPE (Planning, Production, Evaluation). The planning stage included concept analysis, material and fabric characteristics, and design visualization. The production stage consisted of pattern making, material cutting, sewing processes, and finishing. The evaluation stage was conducted through a feasibility test involving three expert panelists and ten trained panelists using assessment instruments covering design, size, aesthetics, sewing techniques, garment performance, and product uniqueness. The results showed that the "Auxora" ready-to-wear garment achieved a feasibility score of 91%, categorized as highly feasible. The percentage scores for each aspect were design 89%, size 90%, aesthetics 82%, sewing techniques 93%, garment performance 96%, and product uniqueness 95%. These findings indicate that "Auxora" is highly feasible as a ready-to-wear fashion product that integrates local cultural values, design innovation, and weaving techniques as its main aesthetic feature.